(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
This paper analyses several principles and peculiarities of mathematical modelling in geography as a branch of science. It discusses the questions like what geography gains from mathematics, how geography synthesizes it, what qualitative features it acquires, what changes the applied-constructive potential of this branch actually undergoes. As a result of the use of mathematical modeling in geography, there is a large increase in the constructive and applied potential of the industry, due to which geography is increasingly being introduced into the economy.